Age changes in basic cranial dimensions in adults - Śmiszkiewicz-Skwarska, Alicja (Anthropological Review, 1978)
Analysed material comprised measurements taken on inhibitans of Włocławek (716 males, 784 females) and craniometry of skeletal sample excavated at Stary Brześć Kujawski (310 males, 196 females). Three anthropometric characters were analysed: skull length (g-op), breadth (eu-eu) and cephalic index. After statistical elaboration of data the author obtained following results: 1. in the modern population both in males and in females skull length increases with age, 2. there is no significant change of this character in the skeletal sample, 3. skull breadth does not undergo significant changes with age in either sample, 4. in the modern sample values of cephalic index decrease with age in response to increasing skull length without concomittant change in skull breadth 5. in the skeletal sample dolichocephalization with age is almost unrecognizable, 6. changes in cephalic index with age in the modern population result from operation of selective factors sensu lato.